Pengaruh Ukuran Perusahaan, Leverage, Pengungkapan Lingkungan, dan Kinerja Lingkungan pada Nilai Perusahaan - Wirawati, Ni Gusti Putu; Dwija Putri, I Gusti Ayu Made Asri; Badera, I Dewa Nyoman (E-Jurnal Akuntansi, 2020)
This study aims to obtain empirical evidence regarding the influence of company size, leverage, environmental disclosure, and environmental performance on the value of the company in the LQ45 Index Companies listed on the Indonesia Stock Exchange in the 2014-2018 period. The sampling method used is purposive sampling. Data analysis techniques using the Multiple Linear Regression test. The results of this study indicate that company size and environmental disclosure have a negative and not significant effect on firm value. This means that the size of the company does not affect the value of the company. Leverage and environmental performance have a positive and significant effect on firm value. This means that the better the environmental performance achieved by the company, the higher the value of the company. Keywords: Company Size; Leverage; Environmental Disclosure; Environmental Performance; The Value Of The Company.